1997
DOI: 10.1126/science.277.5327.834
|View full text |Cite
|
Sign up to set email alerts
|

Natural Behavior Polymorphism Due to a cGMP-Dependent Protein Kinase of Drosophila

Abstract: Naturally occuring polymorphisms in behavior are difficult to map genetically and thus are refractory to molecular characterization. An exception is the foraging gene (for), a gene that has two naturally occurring variants in Drosophila melanogaster food-search behavior: rover and sitter. Molecular mapping placed for mutations in the dg2 gene, which encodes a cyclic guanosine monophosphate (cGMP)-dependent protein kinase (PKG). Rovers had higher PKG activity than sitters, and transgenic sitters expressing a dg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
528
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 518 publications
(545 citation statements)
references
References 32 publications
13
528
0
4
Order By: Relevance
“…The for gene encodes a cGMP-dependent protein kinase (PKG) (Reaume and Sokolowski, 2009). Rover heads exhibit higher levels of for mRNA and higher PKG activity than sitter heads (Osborne et al, 1997). Interestingly, in flies, crowded populations select for animals with rover alleles whereas uncrowded ones select for those with sitter alleles .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The for gene encodes a cGMP-dependent protein kinase (PKG) (Reaume and Sokolowski, 2009). Rover heads exhibit higher levels of for mRNA and higher PKG activity than sitter heads (Osborne et al, 1997). Interestingly, in flies, crowded populations select for animals with rover alleles whereas uncrowded ones select for those with sitter alleles .…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, natural variation in a single gene can be identified that affects the regulation of complex yet distinct behavior patterns (e.g., de Bono and Bargmann, 1998;Krieger and Ross, 2002;Davies et al, 2004;Hammock, 2007). Interestingly, a number of recent achievements in this area involve food-related behaviors and the foraging gene, which encodes a cGMP-dependent protein kinase (PKG) (Osborne et al, 1997;Ben-Shahar et al, 2002Hirose et al, 2003;Fitzpatrick and Sokolowski, 2004;Ingram et al, 2005;Fussnecker and Grozinger, 2008;Garabagi et al, 2008;Heylen et al, 2008;Lucas et al, 2009;Lucas and Sokolowski, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Allelic variation in the for gene encoding PRKG1 homolog in Drosophila results in differences in food-related behaviors. 4,16 The conserved role of PKG in food-related behavior has been demonstrated in the honey bee Apis mellifera 5 and in the nematode Caenorhabditis elegans. 6 Wu et al (2003) 17 speculated that the product of the for gene might be a component of the Drosophila Neuropeptide F (dNPF) signaling pathway, which regulates food-related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…PKG is a transduction pathway enzyme and operates in a variety of cell responses. 3 Allelic variation in the homologs of this gene has been linked to differences in food-related behaviors in fruitflies, 4 honey bees 5 and nematodes. 6 In Drosophila melanogaster, the product of the for gene, encoding PKG, might be a component of the Neuropeptide F (a homolog of human Neuropeptide Y (NPY)) signaling pathway, which is involved in regulation of food-related behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In both laboratory and field trials, homozygous for s individuals exhibit a dispersal‐limited phenotype relative to homozygous for R individuals (more dispersive) (Edelsparre et al., 2014). Individuals homozygous for for s (sitters) are characterized by lower for ‐mRNA expression levels and protein activity (PKG) relative to individuals with the for R allele (rovers) (Osborne et al., 1997). The for R and for s strains used here differ in their second pair of chromosomes where for resides, but share for R ‐derived third and X chromosomes to provide some control for genetic background (de Belle & Sokolowski, 1989; Kaun et al., 2007).…”
Section: Methodsmentioning
confidence: 99%